Stellar gyroscopes: optical design, imaging system and characterisation bed - Aggarwal Kavya (Nanyang Technological University, 2022)
The Attitude Determination and Control System (ADCS) is a satellite subsystem that ensures that the satellite consistently remains oriented in the correct position. For this, attitude determination sensors are placed on board. With the rise of small satellite missions and the need for more pointing accuracy, there is a need to explore more compact, cost-effective attitude determination sensors to improve upon existing sensors while providing more accurate attitude change results. This project focuses on verifying the working principle of a Stellar Gyroscope – an advanced star tracker sensor that can provide precise attitude change results at high operational slew rates. An in-depth analysis of existing attitude determination sensors, their characteristics and disadvantages has been provided to assess the need to implement a Stellar Gyroscope. The imaging system considerations of a Stellar Gyroscope have been evaluated through software-based simulations of the night sky, implementation of a star centroiding algorithm and generation of successive night sky images to evaluate the positional change in captured stars.